Fehlinvestitionen der soziobiologischen Ethnographie und Mädchentötung in Indien - Pfeffer, Georg (Anthropos, 1983)
Sociobiology has become a popular school of ethnological theory in the last decade although it ignores cultural patterns to discuss selected issues as products of natural selection (NS). Particular phenomena are thus "explained" by reference to general hypotheses. As this procedure offers few possibilities of falsification, the issues selected for "explanation" indicate the ideological bias of the school. They happen to include acts of violence and rules of kinship which the sociobiologists can only recognize as ft nepotistic interests." Both issues are always evaluated as "breedingstrategies" in efforts to obtain "inclusive fitness" for the sake of "reproductive success," or vice versa. More than hundred years of sophisticated kinship studies are thereby ignored.— A particular illustration of the so cio bio logical method is a series of essays concerning female infanticide in India. Mildred Dickemann explains 19th century reports of this practice as mate competition within "breeding strategies" for the sake of "reproductive success." Her argument is based on the reports of British authors of colonial times who have obtained certain fame through their racist studies. She ignores all modern works on the wellknown issue of hypergamy and all well-known ethnographic reports which are not in accord with her generalizations. Under the heading of "ecology," this author refers to taxation, crime, and monetary conditions in gross terms to "explain" alleged mating practises. She displays a very limited knowledge of Indian ethnography and revises established reports of others. Thus the ideological content and not the argument itself is to be considered.
Gesehen am 07.10.2024